ANALISIS JENIS FRASA PADA AKUN MARKETING DI MEDIA SOSIAL INSTAGRAM - Assifa Atsna Hanifa; Siti Rinjani (Universitas Singaperbangsa Karawang, 2022)
Syntax is classified as a branch of linguistics (linguistics). Phrases are one of the syntactic units that can be studied. A phrase is defined as a grammatical unit composed of two or more words and does not exceed the limits on the function of clause elements (Ramlan in Rumilah, 2021). This study aims to provide a description of the types of phrases identified in marketing accounts with the usernames @padangpayakumbuah and @erigostore on Instagram social media. Captions for both marketing accounts use varied and interesting phrases, from using phrases in Padang to using non-standard language along with persuasive English. The method used is a qualitative descriptive method with 3 steps, namely: data collection, data analysis, and presentation of the results of the analysis. The technique used is the library, see, and note. The results showed that there were 2 types of phrases in the marketing accounts studied, namely endocentric phrases which included: coordinative (1 finding), attributive (44 findings), and appositive (2 findings), and directive exocentric phrases (18 findings). From the results of this analysis, the type of phrase that dominates is attributive endocentric phrases.